EFEKTIFITAS LEMBAGA SENTRA PENEGAKAN HUKUM TERPADU (GAKUMDU) DALAM MENEGAKKAN KEADILAN PEMILU - Muhammad Ilham Agang (Universitas Borneo Tarakan, 2019)
Abstract Elections are a tangible form of the concept of democracy which is believed to be one form of carrying out government through a